2017
DOI: 10.1016/j.vaccine.2017.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Rabies vaccine is associated with decreased all-cause mortality in dogs

Abstract: Evidence suggests that rabies vaccine may have non-specific protective effects in animals and children. We analyzed four years of data (2012-2015) from an observational study of the health and demographics of a population of owned, free-roaming dogs in a low-income community in South Africa. The objective of this analysis was to assess the association between rabies vaccine and all-cause mortality in dogs, stratified by age group (0-3months, 4-11months, and 12months and older), and controlling for the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…We previously reported results from an observational study in the same population as the current randomized trial [25]. Controlling for the effects of sex and number of dogs in the residence, and stratifying by age, we found that owner-reported rabies vaccination was associated with a lower risk of death from any cause [25].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We previously reported results from an observational study in the same population as the current randomized trial [25]. Controlling for the effects of sex and number of dogs in the residence, and stratifying by age, we found that owner-reported rabies vaccination was associated with a lower risk of death from any cause [25].…”
Section: Discussionmentioning
confidence: 70%
“…Although the randomized, owner-blinded, placebo-controlled design used in the current study provides a more rigorous assessment of the true effect of vaccination on survival than our previous observational study [25], the current study is not without its limitations. The study was designed to detect an overall effect of vaccination on survival, and not effect modification by sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was proposed that rabies vaccine (a non-live vaccine) has protective NSEs in people and in animals [7][8][9]. A recent RCT evaluated the RTS,S malaria vaccine using two parallel age groups: 6 to 12 weeks and 5 to 17 months, with the former control population receiving a serogroup C meningococcal conjugate vaccine and the latter rabies vaccine.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Among several possible explanations, one is that rabies vaccine provide a protective benefit [7,8]. In the age group for which rabies vaccine was used as a control, the control group had 90% lower incidence of meningitis and approximately 50% lower incidence of cerebral malaria In a population-based cohort study, rabies vaccine was shown to be associated with decreased all-cause mortality in free-roaming dogs in a high-mortality setting [9]. Compared to the unvaccinated group, all-cause mortality rates in the vaccine group were lower by 56%, 44% and 16% in young, adolescent and adult dogs, respectively.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%